2012
DOI: 10.1111/j.1365-2621.2012.02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malting and fermentation on antinutrients, and total and extractable minerals of high and low phytate corn genotypes

Abstract: Summary Two corn genotypes, Var‐113 (high phytate) and TL‐98B‐6225‐9 × TL617 (low phytate), were germinated for 6 days. The germinated grains were dried and milled. A mixture of 5% malt and 95% corn flour was fermented for 14 days. Phytic acid and polyphenol contents and hydrochloric acid (HCl) extractability of minerals from the fermented flours were determined at the intervals of 2 days during fermentation. Phytic acid and polyphenol contents decreased significantly (P ≤ 0.05) with an increase in fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Significant reduction of tannins has been noticed in various legume seeds by various authors using similar treatments ( Alegbeleye and Olude, 2009 ). Similarly, the observed reduction in phytic acid in this study might be a result of leaching of phytate ions into the soaking water as explained by Sokrab et al. (2012) .…”
Section: Discussionsupporting
confidence: 65%
“…Significant reduction of tannins has been noticed in various legume seeds by various authors using similar treatments ( Alegbeleye and Olude, 2009 ). Similarly, the observed reduction in phytic acid in this study might be a result of leaching of phytate ions into the soaking water as explained by Sokrab et al. (2012) .…”
Section: Discussionsupporting
confidence: 65%
“…; Sokrab et al . ). Ertaş () reported that the phytic acid content of sprouted lupin flour significantly ( P < 0.05) decreased.…”
Section: Introductionmentioning
confidence: 97%
“…After fermentation, the grains were washed in portable tap water, drained and dried in a hot air oven at 50°C for 4 h before milling. Malting was done using the method of Sokrab et al (2012). Pearl millet grains were steeped in water and spread on a moistened muslin cloth at tropical room temperature.…”
Section: Introductionmentioning
confidence: 99%